Effects of polar κ receptor agonists designed for the periphery on ATP-induced Ca2+ release from keratinocytes. Issue 2 (17th December 2015) - Galla, Fabian; Bourgeois, Christian; Lehmkuhl, Kirstin; Schepmann, Dirk; Soeberdt, Michael; Lotts, Tobias; Abels, Christoph; Ständer, Sonja; Wünsch, Bernhard
Abstract : The very polar pyridylmethyl derivative5a (log  D 7.4 = 1.1) represents a potent and selective full κ-opioid receptor agonist ( K i = 0.13 nM, EC50 = 33 nM), which reduced the release of Ca 2+ -ions into the cytoplasm in human keratinocytes. Abstract : In order to obtain polar κ agonists, which cannot pass the blood–brain barrier, secondary amines3a and3b were reductively alkylated with pyridine-3-carbaldehyde to give pyridylmethyl substituted perhydroquinoxalines5a and5b, respectively. Both5a and5b show very high κ-opioid receptor affinity with K i values of 0.13 nM and 3.8 nM, respectively. Moreover, they are very selective for the κ receptor. In the [ 35 S]GTPγS assay, both quinoxalines reached full agonistic activity. With an EC50 value of 34 nM, 5a is only slightly less potent than the prototypical κ agonist U-69, 593. For the determination of the log  D values, a shake-flask method was developed, making use of quantification by mass spectrometry which requires only very small amounts of the compound (<0.8 mg). According to this method, the log  D 7.4 and log  D 5.4 values of5a were 1.1 and −0.45, indicating very high polarity. The log  D 5.4 value was recorded due the acidic milieu of the skin. Perhydroquinoxalines3–5 reduced the release of Ca 2+ ions into the cytoplasm after stimulation of HaCaT cells with ATP, thereby proving biological activity in human skin cells.